Effects of nandrolone decanoate on the neuromuscular junction of rats submitted to swimming - Cavalcante, W. L. G. [UNESP]; Dal Pai-Silva, M. [UNESP]; Gallacci, M. [UNESP] (Elsevier B.V., 2004)
This study addressed the effects of nandrolone decanoate (ND) on contractile properties and muscle fiber characteristics of rats submitted to swimming. Male Wistar rats were grouped in sedentary (S), swimming (Sw), sedentary+ND (SND), and swimming+ND (SwND), six animals per group. ND (3 mg/kg) was injected (subcutaneously) 5 days/week, for 4 weeks. Swimming consisted of 60-min sessions (load 2%), 5 days/week, for 4 weeks. After this period, the sciatic nerve extensor digitorum longus (EDL) muscle was isolated for myographic recordings. Fatigue resistance was assessed by the percent (%) decline of 180 direct tetanic contractions (30 Hz). Safety margin of synaptic transmission was determined from the resistance to the blockade of indirectly evoked twitches (0.5 Hz) induced by pancuronium (5 to 9 x 10(-7) M). EDL muscles were also submitted to histological and histochemical analysis (haematoxylin-eosin (HE); nicotinamide adenine dinucleotide-tetrazolium reductase (NADH-TR)). Significant differences were detected by two-way ANOVA (p<0.05). ND did not change body mass, fatigue resistance or kinetic properties of indirect twitches in either sedentary or swimming rats. In contrast, ND reduced the safety margin of synaptic transmission in sedentary animals (SND=53.3+/-4.7% vs. S=75.7+/-2.0%), but did not affect the safety margin in the swimming rats (SwND=75.81+/-3.1% vs. Sw=71.0+/-4.0%). No significant difference in fiber type proportions or diameters was observed in EDL muscle of any experimental group. These results indicate that ND does not act as an ergogenic reinforcement in rats submitted to 4 weeks of swimming. on the other hand, this study revealed an important toxic effect of ND, that it reduces the safety margin of synaptic transmission in sedentary animals. Such an effect is masked when associated with physical exercise. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: anabolic-androgenic steroids; swimming; safety margin; neuromuscular junction